Crafting the competitiveness agenda of the Irish state: thenational competitiveness and productivity council - Saqer, Ali (Routledge, Taylor & Francis Group, 2025)
Across Europe, improving living standards and quality of life hasbecome unimaginable without improving competitiveness. Thisfaith in the power of competitiveness is conspicuously strong inthe Irish political discourse. Ireland’s National Competitivenessand Productivity Council is a key site for coordinating thecompetitiveness agenda of the Irish state. It utilizes internationalbenchmarks to construct competitiveness-enhancing policyrecommendations for the Irish government, informing itscompetitiveness strategies. Through a process-tracing analysis,this article examines how the Council-made Irish competitivenessnarrative and recommendations feed into national policy andpolitics. By tracing the journey of the Council’s recommendationsinto the employment, infrastructure and legal services policyareas in Ireland, I show that while the political ambitions ofdomestic actors are anchored in this narrative, the translation ofthe Council’s recommendations into direct policy influence isconditioned by their degree of congruence with the governmentpolitical priorities and the competing interests within the Irishpolitical economy. I underscore how Irish policymakers governwith international benchmarks rather than strictly through them.
Keywords: Competitiveness -- Government policy -- Ireland.; Economic policy -- Ireland.; Infrastructure (Economics) -- Government policy -- Ireland.; Public administration -- Ireland.; Legal services -- Government policy -- Ireland.; Benchmarking (Management) -- Ireland.